Semicrystalline SrTiO3‐Decorated Anatase TiO2 Nanopie as Heterostructure for Efficient Photocatalytic Hydrogen Evolution. Issue 3 (17th February 2022) - He, Yilei; Zhang, Lijuan; Wei, Yanze; Zhang, Xing; Wang, Zumin; Yu, Ranbo
Abstract: The coupling of TiO2 and SrTiO3 through elaborate bandgap engineering can provide synergies for highly efficient photocatalysts. To further improve the separation between photogenerated electrons and holes, a nano‐heterostructured combination of semicrystalline SrTiO3 (S‐SrTiO3 ) and anatase TiO2 nanoparticles is designed, and an optimized interface is achieved between uniformly grown S‐SrTiO3 and metal organic framework (MOF)‐derived anatase TiO2 through a controlled hydrothermal process. Besides tuning of the bandgap and broadening of the absorption spectral range, S‐SrTiO3 particles alleviate charge carrier recombination benefiting from the coupling of the semicrystalline SrTiO3 around the interface. Additionally, highly dispersed S‐SrTiO3 on TiO2 provides a good spatial distribution of active sites and the abundant carbon remained from MOF may reduce charge transport resistance. Moreover, the rapid transfer within the nano‐heterostructure promotes the separation of the photogenerated charge carriers. With the above predominant architecture, when used as a photocatalyst, the as‐synthesized S‐SrTiO3 /TiO2 heterostructure exhibits exceptionally high photocatalytic performance of 13 005 µmol h –1 g –1 for H2 production, exceeding most oxide‐based photocatalysts reported. This study might provide mechanistic insights into a new perspective for the design and preparation of photocatalysts with novel structure and enhanced catalysis activity. Abstract : Semicrystalline SrTiO3 uniformly grows on metal organic framework‐derived TiO2 surface via a simple and facile hydrothermal reaction. The synergy of nano‐heterostructure and semicrystalline effect enables shorter carrier transfer path, lower charge transport resistance, faster electron/hole separating, and stronger interfacial charge coupling, leading to superior photocatalytic hydrogen evolution activity and cycling stability.